Antibacterial and antioxidative activity of O-amine functionalized chitosan. (1st August 2017) - Tamer, Tamer M.; Hassan, Mohamed A.; Omer, Ahmed M.; Valachová, Katarína; Eldin, Mohamed S. Mohy; Collins, Maurice N.; Šoltés, Ladislav
Highlights: O -amine functionalized chitosan has been synthesized and characterized. Antibacterial and antioxidative properties were significantly improved. Thermal stability was enhanced with the incorporation of cinnamaldehyde. Abstract: Cinnamaldehyde was immobilized to O -amine functionalized chitosan via a coupling reaction. Fourier transform infrared spectroscopy confirmed N -cinnamyl substitution. Wetting analyses demonstrate more hydrophobicity in the N -cinnamyl substituted O -amine functionalized chitosan compared to chitosan or unsubstituted O -amine functionalized chitosan. Thermal gravimetric analysis and differential scanning calorimetry demonstrates that the prepared N -cinnamyl substituted O -amine functionalized chitosan exhibits higher thermostability than unmodified chitosan at temperatures in which polysaccharides are commonly stored and utilised. The N -cinnamyl substituted O -amine functionalized chitosan, against four different bacteria strains [two gram-positive ( Staphylococcus aureus and Bacillus cereus ) and two gram-negative ( Escherichia coli and Pseudomonas aeruginosa )], displays promotion of inhibition activity against these bacterial strains. Finally, the antioxidative activity of the N -cinnamyl substituted O -amine functionalized chitosan was compared with those activities of chitosan and O -amine functionalized chitosan. This was evaluated by uninhibited and inhibited hyaluronan degradation and ABTS assay. The N -cinnamyl substituted O -amine functionalized chitosan shows a lower activity towards donating a hydrogen radical compared to chitosan or O -amine functionalized chitosan. On the other hand, the N -cinnamyl substituted O -amine functionalized chitosan exhibited a higher ability to scavenge the ABTS + cation radical compared to chitosan and O -amine functionalized chitosan.